Analisis Pementasan Tari Leko Pada Upacara Dewa Yadnya Di Banjar Tangkup, Desa Kedisan, Kecamatan Tegallalang, Kabupaten Gianyar - Surya Wahyuni, Ida Ayu Ketut; Astuti, Ni Made Dwi Ari; Arniati, Ida Ayu (Jayapangus Press, 2025)
The performance of the Leko Dance at the Dewa Yadnya ceremony in Banjar Tangkup, Kedisan Village, Tegallalang District, Gianyar Regency, has a uniqueness in terms of its performance and its existence is quite rare. This makes the Leko Dance important to study. In this study, the problems to be discussed are focused on two things, namely the reasons for performing the Leko Dance at the Dewa Yajnā ceremony in Banjar Tangkup and the form of the Leko Dance performance. This study uses a qualitative method. Data collection was carried out using observation techniques, in-depth interview techniques, and document study techniques. The technique used to analyze the data is verstehen. The results of the study show that the performance of the Leko Dance is based on the religious encouragement of the community which is based on sincere feelings called ngayah. Mythologically, the performance of the Leko Dance is believed by the Banjar Tangkup community to be a duwe sesuunan at Pura Puseh. The variety of movements and the structure of the presentation of the Leko Dance in Banjar Tangkup are very simple, delivered with soft, flexible and supple movements, consisting of the panglembar and pengipuk parts. In the Leko Dance, two characters appear, namely the male character and the female character. The male character in this case is the role of Natraduwa and the female character is the two nymphs who tempt Natraduwa in his hermitage.